(untitled) (Bangladesh Journal of Medical Microbiology, 2018)
Blood agar is needed for culture of various organisms. As sheep blood is needed for it’s preparation, many small laboratories specially those of rural areas can not prepare it due to difficulty in collection of sheep blood. So, either they do not do the culture or do it without blood agar which cause missing of some important organisms. In this study Brain heart infusion agar was used together with Blood agar to assess it’s efficacy as an alternative of Blood agar. In total 1256 various samples were cultured, on Blood agar , Brain heart Infusion agar and MacConkey agar. Out of 1256 samples 404 samples showed growth of various organisms. It was noted that all bacteria including Enterococcus sp. grew equally in blood agar and BHIA. Brain heart infusion agar can be used as a surrogate of blood agar. Bangladesh J Med Microbiol 2018; 12 (1): 24-26